A low-sintering temperature microwave dielectric ceramic for 5G LTCC applications with ultralow loss. Issue 20 (15th October 2021) - Wang, Dong; Li, Lingxia; Du, Mingkun; Zhan, Yu
Abstract: In next-generation mobile and wireless communication systems, low sintering temperature and excellent dielectric properties are synergistic objectives in the application of dielectric resonators/filters. In this work, Li2 Ti0·98 Mg0·02 O2·96 F0.04 –1 wt% Nb2 O5 (LTMN) ceramics were fabricated, and their sintering temperature was successfully lowered from 1120 °C to 750 °C by adjusting the mass ratio of B2 O3 –CuO (BC) additive. The optimum dielectric properties (ԑr 24.44, Q × f 60, 574 GHz and τ f 22.8 ppm/°C) were obtained in BC-modified LTMN ceramics sintered at 790 °C. Even if their sintering temperature was lowered to 750 °C, the lowest temperature among the Li2 TiO3 -based dielectric ceramics currently used for LTCC technology, excellent dielectric properties (ԑr 23.77, Q × f 51, 636 GHz) were still maintained. Additionally, no extra impurity phase was detected in BC-modified LTMN ceramics co-fired with Ag at 790 °C, indicating that BC-modified LTMN ceramics have a bright prospect in high-performance LTCC devices for 5G applications.